2014
DOI: 10.1016/j.vetmic.2014.04.005
|View full text |Cite
|
Sign up to set email alerts
|

Feline fecal virome reveals novel and prevalent enteric viruses

Abstract: Humans keep more than 80 million cats worldwide, ensuring frequent contacts with their viruses. Despite such interactions the enteric virome of cats remains poorly understood. We analyzed a fecal sample from a single healthy cat from Portugal using viral metagenomics and detected five eukaryotic viral genomes. These viruses included a novel picornavirus (proposed genus “Sakobuvirus”) and bocavirus (feline bocavirus 2), a variant of feline astrovirus 2 and sequence fragments of a highly divergent feline rotavir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
139
0
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 95 publications
(148 citation statements)
references
References 33 publications
(47 reference statements)
8
139
0
1
Order By: Relevance
“…BLAST searches identified 47–102 nt-long elements with 64–74% identity to the FHMPV 5’UTR in the 5’UTRs of porcine sapelovirus 1, bat picornavirus 2 (BPV-2), Feline sakobuvirus A (SakV-A1) and Ia io picornavirus 1 (IiPV-1). These 5’UTRs contain Type IV IRES structures (Hellen and de Breyne, 2007; Lau et al, 2011, 2012; Ng et al, 2014), and the sequence homology with them maps to domain IIIe and flanking regions. A shorter (11–14nt-long) segment of the FHMPV 5’UTR matched precisely to domain IIIe in the Type IV IRESs of avian encephalomyelitis virus (AEV), duck hepatitis A virus 1 (DHAV-1) and Pigeon picornavirus B (PiPV-B) (Hellen and de Breyne, 2007; Kofstad and Jonassen, 2011) and to segments of the 5’UTRs of California sea lion sapelovirus 1 (Csl SapV-1), Ferret parechovirus (FPV) and Pasivirus 1 (PaV-A1).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…BLAST searches identified 47–102 nt-long elements with 64–74% identity to the FHMPV 5’UTR in the 5’UTRs of porcine sapelovirus 1, bat picornavirus 2 (BPV-2), Feline sakobuvirus A (SakV-A1) and Ia io picornavirus 1 (IiPV-1). These 5’UTRs contain Type IV IRES structures (Hellen and de Breyne, 2007; Lau et al, 2011, 2012; Ng et al, 2014), and the sequence homology with them maps to domain IIIe and flanking regions. A shorter (11–14nt-long) segment of the FHMPV 5’UTR matched precisely to domain IIIe in the Type IV IRESs of avian encephalomyelitis virus (AEV), duck hepatitis A virus 1 (DHAV-1) and Pigeon picornavirus B (PiPV-B) (Hellen and de Breyne, 2007; Kofstad and Jonassen, 2011) and to segments of the 5’UTRs of California sea lion sapelovirus 1 (Csl SapV-1), Ferret parechovirus (FPV) and Pasivirus 1 (PaV-A1).…”
Section: Resultsmentioning
confidence: 99%
“…The sole Type III IRES occurs in Hepatitis A virus (genus Hepatovirus )(Brown et al, 1994); Type V IRESs were recently identified in members of the genera Kobuvirus, Salivirus , and Oscivirus (Yu et al, 2011; Sweeney et al, 2012). Type IV IRESs were discovered in Hepatitis C virus (HCV) and Classical swine fever virus (CSFV), members of the genera Hepacivirus and Pestivirus of Flaviviridae , but have subsequently also been identified in several picornavirus genera, including Aquamavirus, Avihepatovirus, Kobuvirus, Megrivirus, Sapelovirus, Senecavirus, Teschovirus , and Tremovirus (Pisarev et al, 2004; Chard et al, 2006a; Hellen and de Breyne, 2007; Kapoor et al, 2008; Reuter et al, 2009; Honkavuori et al, 2011), in the proposed genera Aalivirus (Wang et al, 2014), Anativirus (duck picornavirus TW90A; Hellen and de Breyne, 2007; Tseng and Tsai, 2007), Colbovirus (pigeon picornavirus A (PiPV-A) and PiPV-B; Kofstad and Jonassen, 2011), Kunsagivirus (Boros et al, 2013), Phacovirus (quail picornavirus 1 (QPV-1); Pankovics et al, 2012) and Sakobuvirus (Ng et al, 2014), and in other species, including Bat picornavirus 1 (BPV-1), BPV-2 (Lau et al, 2011) and feline picornavirus 1 (FePV-1)(Lau et al, 2012), that have been provisionally assigned to the genus Sapelovirus .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among these, RVH strains have been identified in humans in parts of Asia and in pigs in Asia and the Americas; however, no genetic relationship among human and porcine strains were reported [136][137][138]. RVI is a putative novel rotavirus species, which has been detected in cats and dogs in Europe and in a feral sea lion in the USA [139][140][141]. Because cats and dogs are thought to be the sources of human infections with RVA, closer monitoring for the zoonotic potential of RVI will be needed.…”
Section: Evidence and Mechanisms Of Rotavirus Zoonosismentioning
confidence: 99%
“…The advent of highthroughput sequencing technology has enabled comprehensive approaches for the simultaneous detection of many viral genomes and the identification of unknown viral genomes without viral isolation (Firth & Lipkin, 2013). Using high-throughput sequencing, viral metagenomics approaches have elucidated whole enteric viromes, resulting in the discovery of unknown viruses in a variety of mammals, including non-human primates, bats, pigs, rodents, cats, sea lions, martens, badgers, foxes, ferrets and pigeons (Baker et al, 2013;Bodewes et al, 2013;Dacheux et al, 2014;Donaldson et al, 2010;Ge et al, 2012;Handley et al, 2012;Li et al, 2010bLi et al, , 2011bNg et al, 2014;Phan et al, 2011Phan et al, , 2013aShan et al, 2011;Smits et al, 2013a;van den Brand et al, 2012;Wu et al, 2012). Further molecular characterization has revealed high nucleotide sequence diversity and unique genome organization of novel viruses (Boros et al, , 2013Li et al, 2010a;Phan et al, 2013b;Sauvage et al, 2012).…”
Section: Introductionmentioning
confidence: 99%